2014
DOI: 10.1373/clinchem.2013.217240
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chromosomally Integrated Human Herpesvirus 6 by Droplet Digital PCR

Abstract: Background Human Herpesvirus-6 (HHV-6) latently infects a majority of adults. In about 1% of the population HHV-6 exists in a chromosomally integrated form (ciHHV-6) that resides in every somatic and germ cell and can be transmitted through the germ line. Patients with ciHHV-6 have been misdiagnosed and unnecessarily treated for active HHV-6 infection, sometimes with significant side effects, based on results from quantitative molecular HHV-6 tests. Methods A droplet digital PCR (ddPCR) assay was developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 30 publications
(39 reference statements)
1
88
0
Order By: Relevance
“…Three days after infection, cells were transferred into a 25-cm 2 flask and cultured with or without BRACO-19 (100 nM) for 21 days. At that point in time, cells were detached using trypsin and DNA was isolated and tested by ddPCR for the presence of HHV-6 and the cellular reference gene RPP30, as described previously (82). U65-U66-specific primers were validated previously (12,83) and used for the detection of the integrated HHV-6 genome.…”
Section: Methodsmentioning
confidence: 99%
“…Three days after infection, cells were transferred into a 25-cm 2 flask and cultured with or without BRACO-19 (100 nM) for 21 days. At that point in time, cells were detached using trypsin and DNA was isolated and tested by ddPCR for the presence of HHV-6 and the cellular reference gene RPP30, as described previously (82). U65-U66-specific primers were validated previously (12,83) and used for the detection of the integrated HHV-6 genome.…”
Section: Methodsmentioning
confidence: 99%
“…13 We used droplet digital (dd)PCR to determine the ratio of HHV-6 DNA to human cells (using human ribonuclease P DNA [RPP30], a reference gene for cell count). 13,16,19 A ratio of 1 6 0.07 was considered positive for iciHHV-6 and distinguished between iciHHV-6 and naturally acquired infection. This assay was validated against a fluorescence in situ hybridizationconfirmed iciHHV-6 cell line.…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…To aid in the recognition of inherited ciHHV-6 in the transplant setting, we recently developed a clinical droplet digital PCR (ddPCR) assay to identify inherited ciHHV-6 in cellular patient specimens (11). A subsequent study demonstrated the utility of ddPCR in distinguishing HHV-6A and -B (12).…”
mentioning
confidence: 99%